2020
DOI: 10.1016/j.engstruct.2020.110573
|View full text |Cite
|
Sign up to set email alerts
|

Optimized seismic retrofit of steel-concrete composite buildings

Abstract: This work is focused on comparatively assessing the cost-effectiveness of three seismic retrofit approaches for non-code-conforming frame buildings with steel-concrete composite columns.The first two of the assessed retrofit approaches aim in indirectly enhancing structural system performance by strengthening individual composite columns using reinforced concrete jackets or concrete-covered steel cages. The third retrofit approach considered aims in upgrading the composite building frame at hand by installing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In a state-of-the art review of strengthening applications with ECC, Shang et al 2019 [23] concluded that the strain-hardening property of ECC renders it an ideal retrofitting material; the interfacial resistance is adequate to ensure monolithic behavior between core and jacket, which is a finding that is also supported by inclined interface shear tests between plain and ECC concrete, particularly if the substrate is roughened prior to the strengthening application. It is also worth mentioning that the results of the present work are in line with the findings of Papavasileiou et al 2020 [24], who demonstrated that implementing a thin jacket layer to a deficient member is an effective retrofit technique that can be competitive to other strengthening methods (such as conventional thicker jackets or bracings at frame bays), provided that the thin jacket is composed of appropriate material(s) to develop sufficient confinement of the core and the additional strength required for the retrofitted member.…”
Section: Envelope Resistance Curvessupporting
confidence: 93%
“…In a state-of-the art review of strengthening applications with ECC, Shang et al 2019 [23] concluded that the strain-hardening property of ECC renders it an ideal retrofitting material; the interfacial resistance is adequate to ensure monolithic behavior between core and jacket, which is a finding that is also supported by inclined interface shear tests between plain and ECC concrete, particularly if the substrate is roughened prior to the strengthening application. It is also worth mentioning that the results of the present work are in line with the findings of Papavasileiou et al 2020 [24], who demonstrated that implementing a thin jacket layer to a deficient member is an effective retrofit technique that can be competitive to other strengthening methods (such as conventional thicker jackets or bracings at frame bays), provided that the thin jacket is composed of appropriate material(s) to develop sufficient confinement of the core and the additional strength required for the retrofitted member.…”
Section: Envelope Resistance Curvessupporting
confidence: 93%
“…Many researchers have done work for estimating the axial strength and strain of externally confined concrete members [17][18][19][20][21][22][23][24] based on empirical techniques [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], i.e., Karbhari et al, Miyauchi et al. [42,43], Lam and Teng [44], and Mander et al [45], as described in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, considerable work on the structural behaviour of CFST has been reported in the literature [17] compared three seismic retrofit strategies for building types with steel-concrete composite columns to find the most efficient strategy. [18] investigated G+7 high-rise buildings with the composite structural system and compared them with RCC structures with the same building plan and design data.…”
Section: Steel-concrete Composite Structuresmentioning
confidence: 99%